2019
DOI: 10.1177/0271678x19887052
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal imaging and evaluation of SAH-associated cerebral large artery vasospasm in mice using micro-CT and angiography

Abstract: Longitudinal in vivo imaging studies characterizing subarachnoid hemorrhage (SAH)-induced large artery vasospasm (LAV) in mice are lacking. We developed a SAH-scoring system to assess SAH severity in mice using micro CT and longitudinally analysed LAV by intravenous digital subtraction angiography (i.v. DSA). Thirty female C57Bl/6J-mice (7 sham, 23 SAH) were implanted with central venous ports for repetitive contrast agent administration. SAH was induced by filament perforation. LAV was assessed up to 14 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…DCI has been reported to correlate with prognosis and neurological function after SAH 25 . Several studies even applied micro‐CT, DSA to longitudinally monitor vasospasm and tried to reveal the progression after SAH 26 . Besides, early brain injury (EBI) encompasses the entire brain injury occurring within 72 h after SAH, which is related to oxidative stress, neuroinflammation, neuronal death, blood‐brain barrier (BBB) damage, autophagy–apoptosis, and ferroptosis 27–30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCI has been reported to correlate with prognosis and neurological function after SAH 25 . Several studies even applied micro‐CT, DSA to longitudinally monitor vasospasm and tried to reveal the progression after SAH 26 . Besides, early brain injury (EBI) encompasses the entire brain injury occurring within 72 h after SAH, which is related to oxidative stress, neuroinflammation, neuronal death, blood‐brain barrier (BBB) damage, autophagy–apoptosis, and ferroptosis 27–30 .…”
Section: Discussionmentioning
confidence: 99%
“… 25 Several studies even applied micro‐CT, DSA to longitudinally monitor vasospasm and tried to reveal the progression after SAH. 26 Besides, early brain injury (EBI) encompasses the entire brain injury occurring within 72 h after SAH, which is related to oxidative stress, neuroinflammation, neuronal death, blood‐brain barrier (BBB) damage, autophagy–apoptosis, and ferroptosis. 27 , 28 , 29 , 30 Although timely and effective treatment is implemented, the SAH‐induced neurological impairments are permanent in individual.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that pathophysiological changes from cerebral vasospasm cause poor prognosis in patients with SAH. 24 However, recent studies have shown that adequate treatment of cerebral vasospasm does not effectively improve the prognosis of these patients. 25 Several studies examining post-SAH EBI have shown that EBI is an important factor affecting the prognosis of patients with SAH.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, the development of large vessel cerebral vasospasm was evaluated by serial intravenous catheter angiography in the SAH perforation model in mice. 39 The authors found a negative correlation of large vessel vasospasm and cerebral perfusion measurement with the survival time of the animals. The correlation of vasospasm with cerebral perfusion as well as survival time is a relevant issue for clinical practice.…”
Section: Discussionmentioning
confidence: 95%